Corrosion investigation of zinc−aluminum alloy matrix (ZA-27) reinforced with alumina (Al2O3) and fly ash. (4th July 2017) - Almomani, Mohammed; Hayajneh, Mohammed T.; Draidi, Majd
ABSTRACT: In this study, zinc−aluminum alloy (ZA-27) matrix composites reinforced by different weight fractions of fly ash or alumina (Al2 O3 ) were produced using the traditional stir casting technique. The corrosion behaviors of both unreinforced alloy and reinforced composites were examined using direct current polarization (DCP) test in a simulated sea solution (3.5 wt.% NaCl). Scanning electron microscopy (SEM) and energy dispersive x-ray (EDX) were used to examine the morphology of the composites' surface before and after corrosion tests. The results of corrosion revealed that reinforcing ZA-27 alloy by fly ash or Al2 O3 particles decreases its tendency to uniform corrosion due to the formation of weak microgalvanic couple between matrix and reinforcement particles. The fly ash and alumina (Al2 O3 ) particles have protected the matrix material from pits formation at early stage of polarization. However, once these pits are formed, they grow faster. Positive hysteresis of the polarization curves implies that the salt layer breakdown and matrix dissolution overshadow surface passivation during the reverse scan. The electrochemical results are consistent with the pits' morphology of the corroded composite. Composites with fly ash reinforcements have autocatalytic pits, whereas composites with alumina (Al2 O3 ) reinforcements have shallow pits.